2019
DOI: 10.1002/jbmr.3730
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Competence and Bone Quality Develop During Skeletal Growth

Abstract: Bone fracture risk is influenced by bone quality, which encompasses bone's composition as well as its multiscale organization and architecture. Aging and disease deteriorate bone quality, leading to reduced mechanical properties and higher fracture incidence. Largely unexplored is how bone quality and mechanical competence progress during longitudinal bone growth. Human femoral cortical bone was acquired from fetal (n = 1), infantile (n = 3), and 2‐ to 14‐year‐old cases (n = 4) at the mid‐diaphysis. Bone quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 60 publications
(160 reference statements)
4
22
0
Order By: Relevance
“…The density of osteocyte lacunae within osteophytes ranged from 400-450 lacunae per mm² bone area. We previously reported that young individuals from both sexes (around 20 years of age) have a total amount of osteocyte lacunae per bone area of 350-450 in the periosteal area of femoral cortexes 29,41 . This confirms that the osteophyte bone tissue quality resembles young bone tissue not just regarding mineralization indices but also with respect to osteocyte number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The density of osteocyte lacunae within osteophytes ranged from 400-450 lacunae per mm² bone area. We previously reported that young individuals from both sexes (around 20 years of age) have a total amount of osteocyte lacunae per bone area of 350-450 in the periosteal area of femoral cortexes 29,41 . This confirms that the osteophyte bone tissue quality resembles young bone tissue not just regarding mineralization indices but also with respect to osteocyte number.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with the irregular collagen fiber arrangement, the lower BMD determined and the large amount of new bone formation, the osteophyte bone consists of woven bone tissue 42 . This newly formed type of bone is generally found in fetal bones 41,43 and with fracture healing 44,45 and is later on replaced by a more organized, lamellar type of bone matrix 41,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…30 The femurs were dehydrated in ascending alcohol concentrations and embedded into polymethyl methacrylate (PMMA). 30 The femurs were dehydrated in ascending alcohol concentrations and embedded into polymethyl methacrylate (PMMA).…”
Section: Analysis Of Mineralizationmentioning
confidence: 99%
“…Segmentation of ROIs is an important task for BAA. MRI and X-ray have different features that are used for BAA that includes local histograms [ 14 , 15 ], image textures [ 16 , 17 ], and structure tensor eigenvalues [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%